Redescription of Dentifibula viburni (Felt) (Diptera: Cecidomyiidae) and review of the genus - Gagné, Raymond J.; Bertone, Matthew A. (Zootaxa, 2022)
Dentifibula viburni (Felt) (Diptera: Cecidomyiidae), type species of Dentifibula Felt, is redescribed with illustrations and compared with its congeners. The genus is differentiated from the generally similar Lestodiplosis Kieffer. As far as presently known, larvae of Dentifibula prey on Diaspididae (Hemiptera: Coccoidea). The nine other species of Dentifibula are diagnosed. Dentifibula ceylanica Felt is removed from synonymy under Dentifibula obtusiloba Felt.